Molecular and morphological evidence of hybridization between native Ruditapes philippinarum and the introduced Ruditapes form in Japan - Shuichi Kitada; Chie Fujikake; Yoshiho Asakura; Hitomi Yuki; Kaori Nakajima; Kelley M. Vargas; Shiori Kawashima; Katsuyuki Hamasaki; Hirohisa Kishino (Conservation Genetics, 2013)
Marine aquaculture and stock enhancement are major causes of the introduction of alien species. A good example of such an introduction is the Japanese shortneck clam Ruditapes philippinarum , one of the most important fishery resources in the world. To meet the domestic shortage of R. philippinarum caused by depleted catches, clams were imported to Japan from China and the Korean peninsula. The imported clam is an alien species that has a very similar morphology, and was misidentified as R. philippinarum (hereafter, Ruditapes form). We genotyped 1,186 clams of R. philippinarum and R. form at four microsatellite loci, sequenced mitochondrial DNA (COI gene fragment) of 485 clams, 34 of which were R. variegatus , and measured morphometric and meristic characters of 754 clams from 12 populations in Japan and China, including the Ariake Sea and Tokyo Bay, where large numbers of R. form were released. Our analyses confirmed that R. form was from the genus Ruditapes , and the genetic differentiation between R. philippinarum and R. form was distinct, but small, compared with five bivalve outgroups. However, R. form had distinct shell morphology, especially larger numbers of radial ribs on the shell surface, suggesting that R. form might be a new Ruditapes species or a variation of R. philippinarum that originated from southern China. A genetic affinity of the sample from the Ariake Sea to R. form was found with the intermediate shell morphology and number of radial ribs, and the hybrid proportion was estimated at 51.3 ± 4.6 % in the Ariake Sea.

Lafutidine can improve the quality of gastric ulcer healing in humans: a randomized, controlled, multicenter trial - K. Higuchi; T. Watanabe; K. Tominaga; M. Shiba; K. Nakagawa; H. Uno; K. Kitada; H. Satoh; S. Chono; N. Oshitani; Y. Fujiwara; T. Arakawa (Inflammopharmacology, 2006)

Peripheral nerve regeneration through alginate gel: analysis of early outgrowth and late increase in diameter of regenerating axons - T. Hashimoto; Y. Suzuki; M. Kitada; K. Kataoka; S. Wu; K. Suzuki; K. Endo; Y. Nishimura; C. Ide (Experimental Brain Research, 2002)

Prediction of drug-drug interactions of zonisamide metabolism in humans from in vitro data - H. Nakasa; H. Nakamura; S. Ono; M. Tsutsui; M. Kiuchi; S. Ohmori; M. Kitada (European Journal of Clinical Pharmacology, 1998)

Changes in urinary 6β-hydroxycortisol/cortisol ratio after birth in human neonates - H. Nakamura; M. Hirai; S. Ohmori; Y. Ohsone; T. Obonai; K. Sugita; H. Niimi; M. Kitada (European Journal of Clinical Pharmacology, 1998)

Molecular evolution of human paramyxoviruses - K. Miyahara; S. Kitada; M. Yoshimoto; H. Matsumura; M. Kawano; H. Komada; M. Tsurudome; S. Kusagawa; M. Nishio; Y. Ito (Archives of Virology, 1992)